OPTIMALISASI PERAN IBU DALAM MENCEGAH WASTING PADA BALITA MELALUI PENDAMPINGAN BERBASIS KOMUNITAS - HARDJITO, KOEKOEH; SENDRA, ENY; ANTONO, SUMY DWI (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2024)
Wasting in toddlers is one of the indicators of malnutrition that can impact serious growth and development in children. Improving nutritional status toddlers need role-important parents, especially mothers, to give intake balanced nutrition. Research This is aimed at evaluating the impact of mentoring a mother toddler on nutritional status children and improving understanding of mother about maintenance nutrition for toddlers. Research This uses a pre-experimental approach with a pre- and post-test design. Intervention mentoring was done during one month against 30 mothers and toddlers in region X, which was implemented through education about giving food, nutrition, and care to children. Nutritional status data of the of the child measured through index weight according to height (BW/H) before and after intervention. In addition, understanding Mother about nutrition for toddlers was measured through test knowledge before and after assistance. Data analysis was carried out with a paired t-test. Before intervention, most nutritional status toddler is on the verge of wasting (approximately -2 SD). After intervention, there is significant improvement, with an average BB/TB approaching the mean value (p < 0.05). Understanding Mother about nutrition also increases significantly after the mentoring program (p < 0.05). Improvements in nutritional status in toddlers show that mentoring mothers is effective in increasing balance nutrition in children. Education customized practical with condition socio-economic local mother becomes key success intervention. An approach that takes into account source Power local help Mother for more easy application of knowledge gained. These results are consistent with a study previously shown that education nutrition based on community can improve nutritional status of children and skills of mothers in parenting. Accompaniment Mother toddler proven effective in improving nutritional status children and understanding Mother about maintenance nutrition, especially in context-limited socio-economic. ABSTRAKWasting pada balita merupakan salah satu indikator malnutrisi yang dapat berdampak serius pada pertumbuhan dan perkembangan anak. Peningkatan status gizi balita membutuhkan peran penting orang tua, terutama ibu, dalam memberikan asupan nutrisi yang seimbang. Penelitian ini bertujuan untuk mengevaluasi dampak pendampingan ibu balita terhadap status gizi anak dan peningkatan pemahaman ibu mengenai perawatan gizi balita. Penelitian ini menggunakan pendekatan pre-eksperimen dengan desain pre dan post-test. Intervensi pendampingan dilakukan selama satu bulan terhadap 30 ibu balita, yang dilaksanakan melalui edukasi tentang pemberian makanan bergizi dan perawatan anak. Data status gizi anak diukur melalui indeks berat badan menurut tinggi badan (BB/TB) sebelum dan sesudah intervensi. Selain itu, pemahaman ibu tentang gizi balita diukur melalui tes pengetahuan sebelum dan sesudah pendampingan. Analisis data dilakukan dengan uji t berpasangan. Sebelum intervensi, sebagian besar status gizi balita berada di ambang wasting (mendekati -2 SD). Setelah intervensi, terjadi peningkatan yang signifikan dengan rata-rata BB/TB mendekati nilai mean (p < 0,05). Pemahaman ibu tentang gizi juga meningkat signifikan setelah program pendampingan (p < 0,05). Perbaikan status gizi balita menunjukkan bahwa pendampingan ibu efektif dalam meningkatkan keseimbangan nutrisi anak. Edukasi praktis yang disesuaikan dengan kondisi sosial-ekonomi lokal ibu menjadi kunci keberhasilan intervensi. Pendekatan yang memperhitungkan sumber daya lokal membantu ibu untuk lebih mudah mengaplikasikan pengetahuan yang diperoleh. Pendampingan ibu balita terbukti efektif dalam meningkatkan status gizi anak dan pemahaman ibu tentang perawatan gizi, terutama dalam konteks sosial-ekonomi yang terbatas.